Pengaruh Kemudahan dan Kepercayaan Terhadap Kepuasan Pengguna Brilink UD. Putra Jaya di Kecamatan Soromandi Kabupaten Bima - Astuti, Puji; Haryanti, Intisari; Muhajirin, Muhajirin (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of ease of use and trust on user satisfaction at BRILink UD. Putra Jaya in Soromandi District, Bima Regency. This research employed a quantitative approach with an associative research design. The population consisted of all users of BRILink UD. Putra Jaya, the exact number of which was unknown. Therefore, the sample size was determined using the Lemeshow formula, resulting in 96 respondents selected through purposive sampling. Data were collected through questionnaires, observations, and literature studies. The data were analyzed using SPSS version 27, including validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t-tests, and F-tests. The results showed that, partially, ease of use had a positive and significant effect on user satisfaction, with a t-value of 3.271 and a significance value of 0.002 (